2018
DOI: 10.1016/j.jvs.2018.03.414
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after elective abdominal aortic aneurysm repair in obese versus nonobese patients

Abstract: Using a large nationally representative database, we demonstrated an increased risk of renal failure and wound infections in obese patients undergoing OAR compared with nonobese patients. On the other hand, obesity did not seem to increase the odds of major adverse outcomes in patients undergoing EVAR. Further long-term prospective studies are needed to verify the effects of obesity after abdominal aortic aneurysm repair and the implications of these findings in clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
(38 reference statements)
2
11
0
Order By: Relevance
“…3,16 There continues to be ambiguity in this area as contradictory results have been reported demonstrating no significant difference in mortality based on BMI alone. 17,21 However, other investigations analyzing outcomes in vascular surgical procedures outside of AAA repair such as lower extremity revascularizations, cerebrovascular procedures, and amputations also show a significant relationship between BMI and mortality. [18][19][20] This study represents a large cohort of patients with rAAA across 2 academic institutions demonstrating the potential predictive value of BMI on perioperative mortality.…”
Section: Discussionmentioning
confidence: 99%
“…3,16 There continues to be ambiguity in this area as contradictory results have been reported demonstrating no significant difference in mortality based on BMI alone. 17,21 However, other investigations analyzing outcomes in vascular surgical procedures outside of AAA repair such as lower extremity revascularizations, cerebrovascular procedures, and amputations also show a significant relationship between BMI and mortality. [18][19][20] This study represents a large cohort of patients with rAAA across 2 academic institutions demonstrating the potential predictive value of BMI on perioperative mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Obese patients are more likely to suffer from postoperative renal failure after AAA repair than non-obese patients. Three of the four studies [12][13][14] used in the meta-analysis described these results. However, one study 15 described obese patients as having a lower chance of postoperative renal failure, but this study scored low on the quality assessment analysis.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, three out of the four studies 12,13,15 and the meta-analysis showed that obese patients were significantly more likely to suffer from wound infections than non-obese patients. DM is a risk factor for surgical site infections for surgery in general, but especially for cardiac surgery.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Data on weight, length, and body mass index were not available, but on the other hand, obesity does not increase the odds of major adverse outcomes in patients undergoing EVAR. 37…”
Section: Discussionmentioning
confidence: 99%